Breaking supervisor-student trust: perspectives of students - Dube, Mbusiseni Celimpilo; Chinaza, Uleanya (Penerbit Universiti Kebangsaan Malaysia, 2024)
Some supervisors do not treat students well and this impacts on trust which can be viewed as a cornerstone for the supervision. The supervisor-student trust is a fragile element of supervision, if not handled with care it can break and thus bringing supervision relationship to an end. Hence supervisors and student should clearly understand their roles in sustaining trust so that they can mould it accordingly. This paper sought to explore issues that can break trust between supervisors and students. It was framed qualitatively and employed semi-structured interviews for data generation. Five themes emerged from analysis of findings. These themes were dehumanising pedagogy/behaviour, treating students as tabula rasa, incompetent supervisor, lack of understanding between the supervisor and co-supervisor and harshness. This paper concludes that some supervisors do not understand that students, as adults, have other responsibilities to take care of on top of the study and some supervisors are not patient with students and that affects trust. Therefore, this paper recommends that supervisors and students discuss terms and conditions of the supervision process so that they clearly define expectations at the early stages of supervision.